Implications of Yedoma bank outcrop on the Arctic river sediment transport - Sergey Chalov; Kristina Prokopeva; Vasily Efimov; Victor Ivanov; Berenger Koffi; Dmitry Botavin; Zygmunt Babinski; Nikita Zimov; Ekaterina Pavlyukevich; Michal Habel (Scientific Reports)
Abstract Our study records the interaction of hydrological and periglacial processes caused by the syngenetic permafrost (yedoma) transformation on the largest Siberian River. Based on field research, remote sensing data and a 2D hydraulic modelling we performed a unique assessment of water discharge, sediment load, and sediment properties on the Duvanny Yar Yedoma (DYY), the World’s largest Ice-Rich and Fine-Grained deposits complex. Rates of bank degradation of the Yedoma (0.10 Mt/year per channel kilometer) are three times those of adjacent river reaches without ice-rich complexes. Bank retreat accelerated 50% for 2001–2021 compared with 1965–1980, leading to a 20% increase in sediment transport below DYY due to silt release by mudflows and sediment resuspension. A sediment plume length reaches up to 80 km below DIY on hot days, caused by an increase in the sum of positive air temperatures leading to the permafrost thawing. Formation of retrogressive thaw slumps is expected within the next decades in the central part of the cliff. We forecast that thermo- and mechanical erosion will lead to rapid sediment delivery at rates that can be a few orders of magnitude larger than those produced by lateral migration. Our research can serve as a reference for the Arctic regions, which are characterized by extremely ice-rich permafrost.